Ventilator Associated Pneunomia in Neonatal Intensive Care Unit: Occurrence and Risk Factors - Fayaz Ahmed, Javaid Iqbal, Faraz Hussain, Khalil Ahmed, Hassan Jabbar, Shabina Ariff, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To examine the occurrence of pneumonia linked with a ventilator in the neonatal intensive care unit and to determine the related risk factors. Purpose of study: To better identify the associated morbidity and mortality, pathophysiology, and recommended measures to avoid this disease, paediatric VAP diagnosis methods must become more standardized and exact. Study design: A cross-sectional study Place and Duration: This study was conducted at Aga Khan University hospital from May 2021 to May 2022 Methodology: This study includes a total of 70 participants admitted in neonatal intensive care unit. All the patients were put under the ventilator for more than 2 days. At the time of admission, the X-ray of the chest was performed, and it was also performed every day. When certain organisms were present on the tracheal aspirate, ventilator-associated pneumonia (VAP) was diagnosed. After 2 days of ventilation, microbial analysis and gram staining were done for tracheal aspirates. They were later examined to determine the occurrence of nosocomial pneumonia and what are the risk factors linked with it. A Chi-square test and t-test were conducted to examine all the data. A confidence level of 0.05 was set. Results: Pneumonia associated with the ventilator occurred in 31.4% of the participants where a large number had developed it between 4-14 days after intubation. There were certain risk factors that were determined in our research. They include the use of H2 blockers, invasive lines, low PaO2/FiO2, and re-intubation. There were two things (use of steroids and enteral feeding through nasogastric) that were not linked with the occurrence of this pneumonia. The patients who were in the group of ventilator-associated pneumonia were having a longer time period of stay and mechanical ventilation. Practical implication: In newborn and paediatric intensive care units, VAP continues to be a significant and unresolved problem. The results of this study will highlight the numerous elements that significantly contribute to ventilator-associated pneumonia. Conclusion: The occurrence of pneumonia associated with ventilators is high. Those patients who were having above mentioned risk factors should require pay special attention towards prevention. Keywords: pneumonia, ventilators, ventilator associated pneumonia, neonatal intensive care unit